Temozolomide and Capecitabine Treatment for an Aggressive Somatotroph Pituitary Tumor: A Case Report and Literature Review - Ishida, Atsushi; Shichi, Hiroki; Fukuoka, Hidenori; Shiramizu, Hideki; Inoshita, Naoko; Yamada, Shozo (Frontiers in Oncology, 2022)
Aggressive somatotroph pituitary tumor that causes acromegaly is extremely rare and resists conventional treatments such as multiple surgeries, radiotherapies, and various types of somatostatin analogs. Here, we propose a novel treatment option for these rare cases by discussing our case and reviewing the literature. We experienced an aggressive somatotroph tumor in a 52-year-old woman with acromegaly. Not only could a complete remission of growth hormone (GH) and insulin-like growth factor-1 (IGF-1) not be obtained, but the tumor continued to grow and eventually recurred around the brainstem despite multidisciplinary treatments. We employed immunohistochemistry and a three-dimensional (3D) spheroid ex vivo assay to determine the best treatment option for this case. Although histology showed strong O6-methylguanine DNA methyltransferase expression and high Ki-67 labeling index (22%), temozolomide (TMZ) combined with capecitabine (CAPTEM) treatment was performed based on the results of the patient-derived 3D spheroid ex vivo assay, which predicted more effective treatment with CAPTEM than with TMZ alone. Consequently, GH and IGF-1 levels were restored to normal range with remarkable tumor shrinkage after CAPTEM treatment. To the best of our knowledge, there have been even very few reports describing successful treatment for such aggressive and refractory somatotroph tumors and this is the first report showing the effectiveness of CAPTEM on refractory somatotroph tumor both ex vivo and in vivo.